THE DIFFERENCE OF SERUM CARBOXY-TERMINAL PROPEPTIDE OF PROCOLLAGEN TYPE I (PIP) IN STAGE A, B AND C HEART FAILURE PATIENTS CAUSED BY HYPERTENSION - Nurul Aini (Acta Interna The Journal of Internal Medicine, 2013)
ABSTRACTIntroduction. Arterial hypertension affects the heart tissue composition which leads to structural remodeling of the myocardium. The imbalance between synthesis and degradation of type I collagen leading to myocardial fibrosis in a form of type I collagen fiber accumulation in the interstitial and perivascular myocardium. Collagen fiber accumulation reduces relaxation stage, diastolic suction, myocardial stiffness and diastolic dysfunction which affect systolic dysfunction leading to heart failure. Concentration of carboxy-terminal pro peptide of pro collagen type I (PIP) in peripheral blood am a synthesis index of type I collagen in HHD. Thus, the measurement of PIP is useful to monitor myocardial fibrosis stage in heart failure and to determine the therapeutic strategy that aims not only to reduce arterial pressure and left ventricular mass but also to prevent myocardial remodeling.Aim of the study. The aim of the study was to ascertain the difference PIP level in patients with the heart failure stage A, B, and C which are caused by hypertension. The serum concentration of PIP was measured by enzyme immunoassay. This research was a cross sectional research designed for cardiology policlinic’s outpatients at Dr. Sardjito General Hospital Yogyakarta from August 2009 until the calculated sample number is fulfilled. Method. One-way ANOVA was used to analyze the differences between the three groups of heart failure stages after being tested for the normality using Kolmogorov-Smirnov normality test. If the result did not show a normal value, a non-parametric test would be undergone using Kruskal-Wallis test followed by Mann-Whitney U test. The differences considered as significant if p < 0.05 with a confidence interval of 95%.Result. The research was performed in 64 patients heart failure caused by hypertension consisted of 22 stages A, 19 stage B and 23 stage C. PIP mean levels of the group stage B 819.78 ± 91,03 ng/ml was higher compared stage A 808.47± 80.8 ng/ml and PIP mean level stage C 852 ± 55.51 ng/ml was higher compared stage B. The PIP mean levels did not differ statistically significantly (p=0. 317).Conclusion. There were no significant differences in serum level of PIP on the stage heart failure A, B and C. Keywords: Collagen, fibrosis, hypertension, heart failure, carboxy-terminal pro peptide